Prediction of retention time of cutinases tagged with hydrophobic peptides in hydrophobic interaction chromatography - Lienqueo, M.E. (2011)
Hydrophobic interaction chromatography (HIC) is an important technique for protein purification, which exploits the separation of proteins based on hydrophobic interactions between the stationary phase ligands and hydrophobic regions on the protein surface. One way of enhancing the purification efficiency by HIC is the addition of short sequences of peptide tags to the target protein by genetic engineering, which could reduce the need for extra and expensive chromatographic steps. In the present work, a methodology for predicting retention times of cutinases tagged with hydrophobic peptides in HIC is presented. Cutinase from Fusarium solani pisi fused to tryptophan–proline (WP) tags, namely (WP)2 and (WP)4, and produced in Saccharomyces cerevisiae strains, were used as model proteins. From the simulations, the methodology based on tagged hydrophobic definition proposed by Simeonidis et al. (Φtagged), associated to a quadratic model for predicting dimensionless retention times, showed small differences (RMSE < 0.022) between observed and estimated retention times. The difference between observed and calculated retention times being lower than 2.0% (RMSE < 0.022) for the two tagged cutinases at three different stationary phases, except for the case of cut (wp)2 in octyl sepharose–2M ammonium sulphate. Therefore, we consider that the proposed strategy, based on tagged surface hydrophobicity, allows prediction of acceptable retention times of cutinases tagged with hydrophobic peptides in HIC.